A Critique of Modernist Synthesis in Islamic Thought - Masudul Alum Choudhury (International Institute of Islamic Thought, 1994)
Is it the realm of theoretical constructs or positive applications that defines the essence of scientific inquiry? Is there unison between the normative and the positive, between the inductive and deductive contents, between perception and reality, between the micro- and macro-phenomena of reality as technically understood? In short, is there a possibility for unification of knowledge in modernist epistemological comprehension? Is knowledge perceived in conception and application as systemic dichotomy between the purely epistemic (in the metaphysically a priori sense) and the purely ontic (in the purely positivistically a posteriori sense) at all a reflection of reality? Is knowledge possible in such a dichotomy or plurality? Answers to these foundational questions are primal in order to understand a critique of modernist synthesis in Islamic thought that has been raging among Muslim scholars for some time now. The consequences emanating from the modernist approach underlie much of the nature of development in methodology, thinking, institutions, and behavior in the Muslim world throughout its history. They are found to pervade more intensively, I will argue here, as the consequence of a taqlid of modernism among Islamic thinkers. I will then argue that this debility has arisen not because of a comparative modem scientific investigation, but due to a failure to fathom the uniqueness of a truly Qur'anic epistemological inquiry in the understanding of the nature of the Islamic socioscientific worldview ...